From Inspiration to Fluency: Investigating the Effects of TED Talks on Speaking Competence in Language Instruction - PATTY, Rafiqa Salwa; TALIB, Ahmad; FARADIBA, Syarifah (Politeknik Negeri Ujung Pandang, 2023)
This article presents the findings of a quantitative study investigating the impact of integrating TED Talks media in language instruction on students' speaking skills. The study focused on assessing the effectiveness of utilizing TED Talks videos as a resource to enhance students' verbal expression and communication abilities. The analysis of pre-test and post-test scores revealed a significant improvement in students' speaking skills following the integration of TED Talks. By incorporating authentic and engaging content from TED Talks, students were exposed to a variety of topics, expert speakers, and real-life language use, leading to enhanced fluency, vocabulary, and pronunciation. These results underscore the potential of integrating TED Talks as an effective pedagogical tool for promoting students' speaking skills in language instruction. Language educators are encouraged to incorporate TED Talks into their teaching practices to create dynamic and interactive learning experiences that foster linguistic development and effective communication. The study contributes to the existing body of research on the use of multimedia resources in language education and offers practical insights for educators seeking innovative approaches to enhance students' speaking abilities.